Ayat-Ayat Al-Qur'an Terkait Manajemen Hubungan Masyarakat dalam Konteks Pendidikan Islam - Febri Sugiyanto; Teresia Ramadani; Sartina Wati; Ivan Fajriyanur (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This article's goal is to investigate the Qur'anic verses related to the quality management of Islamic education. This study employs a literature research method, which involves reviewing various journals and relevant reference books. The findings of his research indicate that quality education is an essential aspect in Islam. Such quality education functions it is not just for the transmission of knowledge, but also for the advancement of positive character and morals. Quality management in Islamic education is very important, especially in building a generation of noble and quality character. The Qur'an, which is the main guide for Muslims, contains quality management principles such as focus on customer satisfaction, leadership based on the example of the Prophet, Process-based approaches, integrated managerial systems, thoughtful decision-making and mutually beneficial relationships, can all be applied in Islamic education to ensure the quality of continuous and ethical learning. With the implementation of this quality management, Islamic education is expected to create a conducive environment for learning, improve the quality of educational outcomes and produce a generation that is prepared to contribute positively to society. Keywords: ,